Análisis de las condiciones de vida de la microempresa formal en el sur de Qutio, en la Parroquia de Chillogallo, en la actividad del comercio. - Narváez Ontaneda, Cristina Alejandra (2013)
The parish of Chillogallo a commercial sector, highlighting the sale of accessories for mobile phones and grocery stores, most owners of microenterprises has the high school level of education, which has not been an impediment to business management. Most business premises are leased and have basic services (water, electricity), which allows a better development in its business, the bulk of micro-entrepreneurs with the help of employees at your local and microentrepreneurs that if they with employees to keep them insured IESS (Social Security Institute). A microentrepreneurs other credits obtained in the last 12 months, between $ 2500 and 3000.